2020
DOI: 10.1111/bph.14943
|View full text |Cite
|
Sign up to set email alerts
|

Trends in use, pharmacology, and clinical applications of emerging herbal nutraceuticals

Abstract: The nutraceuticals market is vast, encompassing many different products with inconsistent levels of evidence available to support their use. This overview represents a Western perspective of the nutraceuticals market, with a brief comparison with that in China, as an illustration of how individual health supplements increase and decrease in popularity in regional terms. Recent changes in sales patterns, mainly taken from the US market, are summarized and a selection of five newer products, which have not been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
173
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 216 publications
(192 citation statements)
references
References 107 publications
(146 reference statements)
0
173
0
Order By: Relevance
“…Therefore, many available products might be ineffective. Meta‐analysis and systematic review studies can be very useful on these kinds of topics in that they help with a comprehensive conclusion that can give the ultimate idea of whether or not to use a specific nutraceutical as effective medicinal agent (Williamson, Liu, & Izzo, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, many available products might be ineffective. Meta‐analysis and systematic review studies can be very useful on these kinds of topics in that they help with a comprehensive conclusion that can give the ultimate idea of whether or not to use a specific nutraceutical as effective medicinal agent (Williamson, Liu, & Izzo, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The analyses enabled a larger number of trials and individuals to be included for meta-analyses, however, could possibly impact mechanism of effectiveness and action, and thus warrants further investigation. Furthermore, due to lack of rigorous regulation, there is a distinct need for the manufacturers of GCE products to prove efficacy, safety, and quality of a marketed product, particularly given such concerns are less strongly enforced than in the pharmaceutical sector (Williamson, Liu, & Izzo, 2019)., which may have influenced the emergence of significant heterogeneity among included studies. Moreover, many available products might be ineffective, and thus require more detailed examination (Williamson et al, 2019).…”
Section: Strength and Limitationsmentioning
confidence: 99%
“…In addition, ASX protects the skin from UVA light-induced oxidation [27]. These biological activities endow ASX with high economic value as a premium health care product, pharmaceutical, and feed additive [28,29].Many studies have shown that after OTA enters the body, it causes damage to multiple tissues such as the kidney [30], liver [31], spleen [32], intestine [33], lung [34], and brain [35]. Therefore, the present study aimed to investigate whether ASX could protect kidney tissue from OTA-induced oxidative stress through the NRF2 pathway and to determine the protective effect of ASX on OTA toxicity in C57BL/J mice treated with OTA.…”
mentioning
confidence: 99%
“…In addition, ASX protects the skin from UVA light-induced oxidation [27]. These biological activities endow ASX with high economic value as a premium health care product, pharmaceutical, and feed additive [28,29].…”
mentioning
confidence: 99%